Factors that Contribute to (or Detract from) Successful Outcomes in African Regional Agreements - Alva, M.; Behar, A. (Washington, DC: World Bank, 2012)
Regional Integration Agreements (RIAs) have proliferated in Africa and the complexity of issues surrounding their formation has increased. This paper describes the different Regional Integration Agreements in Africa, their history, members and reported rationale. It classifies them along three dimensions: 1) according to the different levels of regional integration they have attained; 2) according to three broad triggering motivations for their formation; and 3) according to whether or not they are active. RIAs developed explicitly or exclusively for trade have rarely achieved a high degree of integration. Rather, historical and political features appear to be important in forging bonds between countries. This preliminary investigation finds no conclusive evidence of increased trade, nor of diversion in trade patterns.